Changes in expression levels of oxidative stress‐related genes in mouse epididymides by neonatal exposure to low‐dose decabromodiphenyl ether. (31st December 2013) - Nakamoto, Makoto; Miyaso, Hidenobu; Komiyama, Masatoshi; Matsuno, Yoshiharu; Mori, Chisato
Abstract: Decabromodiphenyl ether (decaBDE), one of the polybrominated diphenyl ethers (PBDEs), is the most well‐known flame retardant and is used worldwide. In a previous study, we identified adverse effects of neonatal decaBDE exposure on mouse epididymides, such as decreased epididymal weight. On the other hand, neonatal exposure to diethylstilbestrol (DES), an artificial estrogenic compound, also causes several adverse effects on epididymides. DES exposure results in decreased epididymal weight, morphological abnormalities, and permanent alterations in the expression levels of several genes. The molecular mechanisms underlying the harmful effects of decaBDE exposure remain unclear. Many studies have reported that PBDEs have estrogenic activity, which may contribute to the induction of the adverse effects of decaBDE exposure. We aimed to examine the effects of neonatal decaBDE exposure on epididymides. Our data showed that (1) no histological change was observed on epididymal tissues from neonatal decaBDE exposure, unlike the effect of DES, (2) decaBDE exposure did not induce the alterations in gene expression observed with DES exposure; instead alterations in gene expression of certain oxidative stress‐related genes were observed, and (3) the expression of ubiquitin C increased in decaBDE‐exposed mouse epididymides. Our present data suggest the possibility that increased oxidative stress plays a role in the harmful effects observed in mouse epididymides after decaBDE‐exposure.